Protection of the Work Rights of Heroines - Setia Indira, Putri; Jasmaniar, Jasmaniar; Muin, Sri Amlinawaty (Qawanin Jurnal Ilmu Hukum, 2025)
Abstract: This study aims to analyze the regulation of civil law in Indonesia concerning the protection of women workers' reproductive rights and the application of civil law in employment contracts related to these rights. The research employs an empirical legal research method. The findings reveal two main points: First, the protection of women workers' reproductive rights in Makassar has been partially implemented, such as maternity leave, but rights related to menstrual leave, pregnancy leave, and breastfeeding facilities remain inadequate. Second, the application of civil law in employment contracts for women workers is not yet optimal. The contributing factors include the need to enhance monitoring and enforcement of regulations regarding women workers' reproductive rights. Education for companies and workers is also necessary to raise awareness and compliance. Additionally, more specific regulations are required to ensure the effective implementation of these protections in Makassar. Keywords: Legal Protection, Reproductive Rights, Women Workers/Laborers Abstrak: Penelitian ini bertujuan untuk menganalisis pengaturan hukum perdata di Indonesia terkait perlindungan hak reproduksi pekerja/buruh wanita dan penerapan hukum perdata dalam kontrak kerja yang berkaitan dengan hal tersebut. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum empiris. Hasil penelitian menunjukkan dua hal utama: Perlindungan hak reproduksi pekerja wanita di Makassar sudah diterapkan sebagian, seperti cuti melahirkan, namun hak terkait cuti haid, cuti hamil, dan fasilitas menyusui masih kurang dan Penerapan hukum perdata dalam kontrak kerja pekerja wanita belum optimal. Kemudian yang menjadi alasan antara lain adalah meningkatkan pengawasan dan penegakan aturan terkait hak-hak reproduksi pekerja wanita. Edukasi kepada perusahaan dan pekerja juga perlu dilakukan untuk meningkatkan kesadaran dan kepatuhan. Selain itu, aturan yang lebih spesifik diperlukan agar implementasi perlindungan hak-hak tersebut dapat berjalan lebih efektif di Kota Makassar. Kata Kunci: Perlindungan Hukum, Hak-Hak Reproduksi, Pekerja/Buruh Wanita